Repetitive Head Trauma Induces Chronic Traumatic Encephalopathy by Multiple Mechanisms - Cherry, Jonathan D.; Babcock, Katharine J.; Goldstein, Lee E. (Seminars in Neurology, 2020)
Exposure to repetitive neurotrauma increases lifetime risk for developing progressive cognitive deficits, neurobehavioral abnormalities, and chronic traumatic encephalopathy (CTE). CTE is a tau protein neurodegenerative disease first identified in boxers and recently described in athletes participating in other contact sports (notably American football, ice hockey, rugby, and wrestling) and in military veterans with blast exposure. Currently, CTE can only be diagnosed by neuropathological examination of the brain after death. The defining diagnostic lesion of CTE consists of patchy perivascular accumulations of hyperphosphorylated tau protein that localize in the sulcal depths of the cerebral cortex. Neuronal abnormalities, axonopathy, neurovascular dysfunction, and neuroinflammation are triggered by repetitive head impacts (RHIs) and likely act as catalysts for CTE pathogenesis and progression. However, the specific mechanisms that link RHI to CTE are unknown. This review will explore two important areas of CTE pathobiology. First, we will review what is known about the biomechanical properties of RHI that initiate CTE-related pathologies. Second, we will provide an overview of key features of CTE neuropathology and how these contribute to abnormal tau hyperphosphorylation, accumulation, and spread.
Keywords: chronic traumatic encephalopathy (CTE); concussion; neurodegeneration; tau protein traumatic brain injury (TBI)